Strategi Guru dalam Membentuk Green Behaviour melalui Pembelajaran Ekopedagogi di Sekolah Dasar - Romadhon, Sahrul; Oktafiana, Shinta; Risdiana, Faraniena Yunaeni (GHANCARAN: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2024)
Ecopedagogy learning is important to implement in an effort to preserve the environment and shape students' Green behaviour. This study aims to describe the teacher's efforts in internalising Green behaviour in students through learning. This research uses descriptive qualitative research with observation and interview data collection techniques. This research was conducted in elementary schools in Tlanakan sub-district that have integrated learning with environmental awareness. The results of this study are that there are three Green behaviours, namely caring for the earth, caring for the surrounding environment and being wise in waste management. The teacher's strategy in shaping the behaviour of caring for the earth by making slogans, habituation of bringing bottles and providing examples. Caring for the environment by planting local plants, greening and processing organic waste as fertiliser. Wise in waste management by joining the P5 project by making creations from used goods, ecoprint batik and saving waste in plastic bottles. The internalisation of Green behaviour provides many benefits to students' behaviour in protecting the environment. And the strategies carried out by teachers provide direct experience and learning.